COMMUNICATION STRATEGY APPLIED BY FRONT OFFICE STAFF - Nugraha, I Gede Surya Dharma (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Some still think when talking to guests and do not speak English very well. In addition, the receptionist is also still convoluted in explaining something. This problem has an impact on poor service. This study aimed to analyze the type of strategic communication used by the front office staff of the Intercontinental Bali Resort. Types of strategic communication used by staff, and reasons for strategic communication used by staff. The subject of this research is the front office staff at the Intercontinental Bali Resort. This study uses a qualitative design. Data collection methods are observation, interviews, and voice recordings. The results showed five types of strategic communication implemented by the front office staff at the Intercontinental Bali Resort, namely: Paralanguage had the highest percentage of strategic communication with a percentage of around (48%). The most widely used strategy by staff is the Clarification Hole strategy with a percentage (37%). The most frequently used is an approximation in percentage (11%). Then fourth, there are (2) communication strategies used mainly by staff. There are languages with a percentage of 2% for each strategy. Paralanguage is a communication strategy used to provide more information so that guests can imagine clear things, the contact that occurs, and make the conversation more polite because it will be the first glance at this time.